Precession-paced late Maastrichtian bottom-water dynamics - Fischer, Alexa; Batenburg, Sietske J.; Bahr, André; Voigt, Silke; Rheinberger, Anne; Schmickal, Sarah; Rheinberger, Silvia; Greule, Markus; Rheinberger, Stefan; Friedrich, Oliver (Communications earth & environment, 2025)
The long-term global cooling of the Late Cretaceous was interrupted by an intense warming period at ~69 Ma known as the mid-Maastrichtian event. The underlying mechanisms of this climatic event and associated change in the global carbon cycle are, however, strongly debated, including a possible major reorganization of deep-ocean circulation patterns. How this reorganization co-varied with climate shifts and global carbon cycling is not known, mainly due to the lack of high-resolution studies. Here, we present new high-resolution stable isotope, Mg/Ca-derived bottom-water temperature, and CaCO3 wt% records from IODP Site U1403 (North Atlantic) to reconstruct the climatic and oceanographic processes associated with the mid-Maastrichtian event. We observe a very dynamic and vigorous deep-ocean circulation that is characterized by precession-paced fluctuations that are proposed to reflect the interplay of different bottom-water source regions. Our results further point towards Large Igneous Province volcanism as a trigger not only for the mid-Maastrichtian event but also for the observed change in deep-water circulation. A clear shift towards the dominance of Northern Component Water bathing the North Atlantic at around 68 Ma signals the end of low-latitude waters in the North Atlantic, a bottom-water source that characterized the Cretaceous oceans for tens of millions of years.